A STUDY OF THE CHANGING CONSUMER BUYING BEHAVIOUR IN ORGANISED RETAILING IN LUCKNOW CITY - Ahmad, Zubair (International Journal of Engineering Technologies and Management Research, 2020)
The major factor of consumer behaviour in organised retailing is the changing buying behaviour. Various management thinkers have conducted several studies to understand the relationship of buying behaviour and organised retailing. Consumer behaviour is defined as the behaviour that consumers display in searching for, purchasing, using, evaluating and disposing of products and services that they expect will satisfy their needs. (L.G. Schiffman, L.L. Kanuk, 2005). Consumer buying behaviour is changes due to organised retailing sector which introduce in India in 2000 year. Slowly organised retail flourish in India year after year and till 2008 many malls and other hypermarkets open in many cities of India. In this sector some Indian players took the initiative and open their retail chains. For example Future Group opened Big Bazaar, RPG Group opened Spencer Store, Ruia Group opened Shoppers Stop in many cities Now-a-days employees have been hired, trained and remunerated in organised sector. In this respect the malls and hypermarkets provide job opportunities to many people in the country. The organised retailing changes a lot the “consumer buying behaviour” in the country. Under one roof the whole items related to each category available to the consumers in the shops. Times have changed people want a good shopping experience and this experience they feel in purchasing the products from malls, hypermarkets etc. The purpose of this study was to identify through hypothesis testing how consumer buying behaviour changes in organised retailing. The study was conducted using structured questionnaire on private and public sector employees. Chi- Square technique was applied and chi value was computed to test the formulated hypothesis in order to find relevance of consumer buying behaviour in organised retailing.